A look at clinical applications and developments of photodynamic therapy - Arménio Serra; Marta Pineiro; Nelson Pereira; António Rocha Gonsalves; Mafalda Laranjo; Margarida Abrantes; Filomena Botelho (Frontiers Media S.A., 2011)
The battle against cancer is so important that all possible weapons must be considered. Photodynamic therapy (PDT) is a therapeutic approach which has proved its capacity to give many excellent results, but it is having some difficulty in being imposed. The simplicity of the mechanism of action of this technique has been compromised by the multidisciplinary approach required for its implementation, which makes its adoption for more general use by health professionals difficult. This review aims to give a perspective of the performance of current approved PDT drugs, and their clinical applications against cancer. Basic investigation in PDT, particularly in the design of new sensitizers, is still ongoing, and needs to be further exploited. Emergent and diversified solutions with excellent results in pre-clinical phases are described to raise the multidisciplinary interest required to boost the clinical use of PDT.